RANCANGAN SISTEM INFORMASI KOST PUTRI MALIKA BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL DAN MYSQL - Dwi Kartinah (Asosiasi Dosen Muda Indonesia, 2022)
This scientific writing discusses the creation of a website for the registration and reservation process at Putri Malika's Kost. With this website, it is hoped that it can assist the patient registration and reservation process, so that prospective boarding house occupants no longer need to register or make reservations manually. Apart from that, this website is also expected to help the process of recording user data that makes reservations. The research method used is the System Development Life Cycle (SDLC). The stages in the SDLC method are planning, analysis, design, implementation and testing of the system. Making this website uses the Laravel framework and MySQL as the database. This website can be accessed via the address https://www.teamstart.my.id/. Based on the results of trials conducted in this study, it can be concluded that the registration and reservation website for prospective residents of the Putri Malika Boarding House was successfully created and can be used by prospective residents and boarding house residents to register or make reservations and receive notifications of billing and payment history, as well as assisting the data collection process. boarders and registrars